Hölderlin’s and Novalis’ Philosophical Beginnings (1795) - Manfred Frank (Humanities)
Philosophers and literary scholars have notoriously struggled with the periodization of Hölderlin’s work, showing particular reluctance to situate it within Early Romanticism. But there can be no doubt that Hölderlin’s philosophical work resides within the context of an anti-foundationalist criticism, which students of Karl Leonhard Reinhold leveled at his programmatic deduction from a “highest principle” (oberster Grundsatz) in the early 1790s and intensified following Fichte’s lectures (1794/95) on the Science of Knowledge (Wissenschaftslehre). Novalis belonged directly to the circle of Reinhold students, while Hölderlin gained access to it through Friedrich Immanuel Niethammer, his friend from student days in Tübingen and “mentor” in Jena. Niethammer encouraged both Hölderlin and Novalis to contribute to his Philosophisches Journal, conceived as a forum for discussing the pros and cons of foundational philosophy (Grundsatzphilosophie). Novalis’ Fichte-Studies and Hölderlin’s philosophical fragments from 1795/96 can be read as drafts for such an essay. Both men developed similar critiques of Reinhold’s reformulated, subject-centered “highest principle”, the “principle of consciousness” (Satz des Bewusstseins). They argued that according to Reinhold, self-consciousness is a representation, i.e., a binary relationship that provides no explanation for the certainty of unity associated with self-consciousness. Both postulate a transcendent “ground of unity”, which would address this issue while remaining inaccessible to consciousness. My article demonstrates that both men failed to disentangle themselves from the snares of Reinhold’s model of representation, and both transferred the solution for the problem of self-consciousness onto the extra-philosophical medium of art.